CONFRONTATION AND RECONCILIATION: Muslim Voices of Maluku Conflict (1999-2002) (JOURNAL OF INDONESIAN ISLAM, 2007)
This paper seeks to examine some of the perceptions and attitudes developed by Muslims in relation to the social conflict of Maluku. This paper argues that there were no single views among Muslims with regard to the conflict. Some Muslim hard-liners in general have demonstrated hostile perceptions and confrontational attitudes toward their perceived enemy. They constructed the conflict as a “religious war,” and demanded that the Indonesian Council of Religious Scholars (MUI) issue a fatwa that would allow Muslims outside Maluku to fight against the enemy in Maluku. The Muslim moderates, on the other hand, tended to avoid religious vocabularies, while attempting to work out peaceful solutions. The semi-official MUI, Nahdlatul Ulama, and Muhammadiyyah perceived the conflict as not religiously driven; they viewed the conflict in a more sophisticated way. They saw no need to wage a religious war and no need to issue a fatwa for a national jihad.